Prevalence of Anal Dysplasia in Human Immunodeficiency Virus–Infected Transgender Women. Issue 11 (November 2017) - Kobayashi, Takaaki; Sigel, Keith; Gaisa, Michael
Abstract : Abstract: Although human immunodeficiency virus–infected men who have sex with men are at high risk for anal cancer, little is known about the prevalence of anal dysplasia in human immunodeficiency virus (HIV)-infected transgender women. Our study found that prevalence rates of abnormal anal cytology and histology in HIV-infected transgender women were similar to those in HIV-infected men who have sex with men. Abstract : The prevalence rates of abnormal anal cytology and histology in human immunodeficiency virus–infected transgender women were similar to those in human immunodeficiency virus–infected men who have sex with men.